Research on Parallel Assembly Sequence Planning of Vertical Planetary Gearboxes Based on the Ant Colony Algorithm - Xu Wentao; Zhang Liyong; Zhi Yanfeng; Li Tongjie; Wang Juan; Wang Changlu; Jiang Yehu; Chen Jijie; Wang Wenxiang (Jixie chuandong)
The increase of parts in the assembly leads to the complexity of the assembly process and technology, the planning of the assembly sequence has become more rigorous, and the computer-aided assembly sequence planning has become an important direction of virtual assembly. In this study, taking vertical planetary gearbox as an example, assembly coupling undirected relation diagram is used to determine the assembly coupling relation, and the assembly association matrix is transformed into mathematical information. Then through the in-depth study of ant colony algorithm, the assembly path is planned. The results show that the assembly time of the vertical planetary gearbox is reduced by 20%, and human resources are saved by 1/3.